In Silico Evaluation of Quercetin Methylated Derivatives on the Interaction with Secretory Phospholipases A2 from Crotalus durissus terrificus and Bothrops jararacussu - Belchor, Mariana Novo [UNESP]; Costa, Caroline Ramos da Cruz [UNESP]; Roggero, Airam [UNESP]; Moraes, Laila L. F. [UNESP]; Samelo, Ricardo [UNESP]; Annunciato, Isabelly [UNESP]; de Oliveira, Marcos Antonio [UNESP]; Sousa, Sergio F.; Toyama, Marcos Hikari [UNESP] (MDPI, 2023)
Quercetin derivatives have already shown their anti-inflammatory potential, inhibiting essential enzymes involved in this process. Among diverse pro-inflammatory toxins from snake venoms, phospholipase A2 is one of the most abundant in some species, such as Crotalus durissus terrificus and Bothrops jararacussu from the Viperidae family. These enzymes can induce the inflammatory process through hydrolysis at the sn-2 position of glycerophospholipids. Hence, elucidating the main residues involved in the biological effects of these macromolecules can help to identify potential compounds with inhibitory activity. In silico tools were used in this study to evaluate the potential of quercetin methylated derivatives in the inhibition of bothropstoxin I (BthTX-I) and II (BthTX-II) from Bothrops jararacussu and phospholipase A2 from Crotalus durissus terrificus. The use of a transitional analogous and two classical inhibitors of phospholipase A2 guided this work to find the role of residues involved in the phospholipid anchoring and the subsequent development of the inflammatory process. First, main cavities were studied, revealing the best regions to be inhibited by a compound. Focusing on these regions, molecular docking assays were made to show main interactions between each compound. Results reveal that analogue and inhibitors, Varespladib (Var) and p-bromophenacyl bromide (BPB), guided quercetins derivatives analysis, revealing that Leu2, Phe5, Tyr28, glycine in the calcium-binding loop, His48, Asp49 of BthTX-II and Cdtspla2 were the main residues to be inhibited. 3MQ exhibited great interaction with the active site, similar to Var results, while Q anchored better in the BthTX-II active site. However, strong interactions in the C-terminal region, highlighting His120, seem to be crucial to decreasing contacts with phospholipid and BthTX-II. Hence, quercetin derivatives anchor differently with each toxin and further in vitro and in vivo studies are essential to elucidate these data.
Keywords: inflammation; molecular docking; natural compounds; snake venoms; toxins